The Influence of the Quality of Accounting Information Systems and Top Management Support on the Quality of Financial Statements - Lutfia Lutfia; Arlis Dewi Kuraesin (Kusuma Negara Business School, 2021)
This study aims to determine the effect of accounting information systems and top management support on the quality of financial reports. The purpose of this research is the author is to analyze and obtain empirical evidence of the influence of the quality of accounting information systems and top management support on the quality of financial reports. The population of this research is in the section of the Directorate of Financial Services and BUMN at the Ministry of National Development Planning/Bappenas. The research sample used was 40 people with data sources obtained through the results of filling out a questionnaire. The sampling method and the data used are primary data, using SPSS version 23 data processing. The results showed that the quality of the accounting information system and top management support had an effect on the quality report.